A Pragmatic Competence Analysis of English Expressive Acts by Col Language Speakers in Lubuklinggau - Sastika Seli; Dewi Syafitri; Citra Raflesia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research aims to explain the pragmatic competence of Col language speakers who live in Lubuklinggau. The subject of the research is 20 Col language speakers who live in Lubuklinggau and are learning or have learnt English for at least six months. To collect the data, Discourse Tests, Interview and Observation were conducted. The result shows that most of the informants applying the similar strategy in respond to the situation given. In some acts they understand to use the expression appropriately but they failed to understand the more appropriate expression in a formal situation. Keywords: Col Language, Discourse Test, English Pragmatic Competence, Expressive Acts